Alumina-titanium oxide composite oxide and preparation method and application thereof

The alumina-titanium oxide composite oxide is prepared by combining co-precipitation method with hydrothermal method, which solves the problem of difficulty in forming anatase crystal form at low titanium oxide content in the prior art, and realizes the preparation of alumina-titanium oxide composite oxide with high pore concentration and suitable pore size, which is suitable for hydrogenation catalyst support.

CN119838587AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311346007.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

In the prior art, when preparing alumina-titanium oxide composite oxide, it is difficult to form anatase crystal form at low titanium oxide content, and the process is complex, the raw materials are expensive, and industrial production is difficult.

Method used

The co-precipitation method is used in combination with the hydrothermal method, and the alumina-titanium oxide composite oxide is prepared through gel formation reaction, aging reaction and hydrothermal treatment, and the titanium oxide content is controlled to be low and the anatase crystal form.

Benefits of technology

The preparation of alumina-titanium oxide composite oxide with anatase crystal form is achieved at low titanium oxide content, which improves the pore concentration and the maximum pore size. It is suitable for a carrier for hydrogenation catalysts, with simple process and cheap raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838587A_ABST
    Figure CN119838587A_ABST
Patent Text Reader

Abstract

The invention relates to the field of hydrogenation reaction and discloses an aluminum oxide-titanium oxide composite oxide as well as a preparation method and application thereof. The invention relates to a preparation method of an aluminum oxide-titanium oxide composite oxide, which comprises the following steps: (1) carrying out gelling reaction on an acid solution containing aluminum and titanium and an aluminum-containing alkaline solution to obtain a solid gelling product; (2) in the presence of a precipitator, carrying out aging reaction on the solid gelling product obtained in the step (1) to obtain an aging reaction product; (3) carrying out hydrothermal treatment on the aging reaction product obtained in the step (2), and then drying and roasting to obtain an aluminum oxide-titanium oxide composite oxide; wherein the temperature of the hydrothermal treatment is higher than that of the aging reaction. The method can realize preparation of the alumina-titanium oxide composite oxide with low titanium oxide content and a specific crystal form without using an organic titanium-containing reagent, and is more environment-friendly and easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogenation reaction, and in particular to an aluminum oxide-titanium oxide composite oxide and a preparation method and application thereof. Background Art

[0002] The pore structure of the support of the hydrogenation catalyst and its interaction with the active metal have an important influence on the catalytic performance. 4+ Due to its high-temperature reducibility, the hydrodesulfurization catalyst prepared with titanium dioxide as a carrier shows high reaction activity and good anti-coking performance. However, due to the small specific surface area and pore volume of titanium dioxide and its poor thermal stability, its application as a catalyst carrier is limited. Combining titanium dioxide with alumina can effectively improve thermal stability, greatly improve the pore structure, and show high reaction activity in the hydrodesulfurization reaction. The anatase crystal form plays a major role in improving the activity of the hydrodesulfurization reaction. In the existing titanium-aluminum composite oxides synthesized by coprecipitation, when the titanium dioxide content is low, titanium dioxide is dispersed in alumina and cannot form an anatase phase that is more conducive to the hydrodesulfurization reaction.

[0003] Patent application EP0339640A1 discloses the synthesis of alumina-titania composite materials by co-precipitation of water-soluble aluminum salts and titanium salts. Sodium aluminate aqueous solution is used as an alumina source and TiOCl2 and / or TiCl3 and / or TiOSO4 solution is used as a titanium dioxide source. The two are added to the reactor in parallel. During the process, corresponding HCl or H2SO4 is added to control the pH value. During the reaction, the reactor temperature is maintained at about 50-57°C. After intense mixing, the alumina-titania material is obtained after filtration, drying and roasting. Compared with the traditional impregnation method, the titanium dioxide in the composite oxide material prepared by the co-precipitation method is distributed in the alumina and does not show anatase peak.

[0004] Patent application CN1344586A discloses a supported nano-TiO2 composite carrier and a preparation method thereof, wherein the method prepares a titanium sol by mixing butyl titanate with ethanol, water and nitric acid, adds the titanium sol to a slurry obtained by mixing pseudo-boehmite with water or anhydrous ethanol, and places the sample in air for natural drying for 24 hours, 12 hours at 60°C, 4 hours at 120°C, and then calcined at 200, 300, 400, and 500°C for 2 hours in sequence. The method can load nano-TiO2 on macroporous alumina, and XRD results show that the crystal form of nano-TiO2 is anatase.

[0005] Patent application CN111050904A discloses a series of methods for synthesizing titanium-aluminum composite oxide carriers, including co-extrusion, co-precipitation, continuous step-by-step precipitation and impregnation. Among them, the co-precipitation method is to add aluminum sulfate and titanyl sulfate mixed in a fluid, as well as sodium aluminate, to water at 60°C and pH 8.5. The flow rate of sodium aluminate and aluminum sulfate / titanic sulfate is fixed, and the pH is constantly controlled by NaOH or H2SO4. After the addition is completed, the pH is raised to 10 and aged, and then filtered, washed, dried and roasted to obtain a titanium-aluminum composite oxide material. The titanium-aluminum carrier prepared by this method has a relatively high content of TiO2 (mass ratio is 20.9% and 48.0%, respectively), and the characteristic peaks of anatase are shown in the XRD results.

[0006] When the content of titanium oxide is relatively low, the coprecipitation method cannot obtain anatase-type titanium-aluminum composite oxide material. When nano-titanium dioxide is loaded onto an alumina carrier by the sol-gel method, the synthesis process is relatively complicated and cannot be prepared using cheap and readily available raw materials and simple means. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems existing in the prior art and provide an aluminum oxide-titanium oxide composite oxide and a preparation method and application thereof. The method can realize the preparation of an aluminum oxide-titanium oxide composite oxide with a low titanium oxide content and a specific crystal form without using an organic titanium-containing reagent, which is more environmentally friendly and easy to industrialize.

[0008] In order to achieve the above object, the present invention provides a method for preparing an aluminum oxide-titanium oxide composite oxide in a first aspect, wherein the method comprises the following steps:

[0009] (1) subjecting an acidic solution containing aluminum and titanium to a colloid reaction with an alkaline solution containing aluminum to obtain a solid colloid product;

[0010] (2) subjecting the solid gel-forming product obtained in step (1) to an aging reaction in the presence of a precipitant to obtain an aging reaction product;

[0011] (3) subjecting the aging reaction product obtained in step (2) to hydrothermal treatment, followed by drying and calcining to obtain an aluminum oxide-titanium oxide composite oxide;

[0012] Among them, the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction.

[0013] The second aspect of the present invention provides an aluminum oxide-titanium oxide composite oxide prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides a use of the aluminum oxide-titanium oxide composite oxide described in the second aspect in a hydrodesulfurization reaction.

[0015] Compared with the prior art, the method provided by the present invention adopts a coprecipitation method combined with a hydrothermal method to prepare an aluminum oxide-titanium oxide composite oxide, and can achieve the preparation of an aluminum oxide-titanium oxide composite oxide without using an organic titanium-containing reagent. Preferably, the method provided by the present invention is more suitable for the preparation of an aluminum oxide-titanium oxide composite oxide with a low titanium oxide content and anatase crystal form; further, the method provided by the present invention has a simple process, cheap and easily available raw materials, easy-to-control operating conditions, and adjustable product properties.

[0016] The aluminum oxide-titanium oxide composite oxide provided by the invention has a low titanium oxide content, anatase-type titanium oxide, a high pore concentration and a most probable pore diameter within a suitable range, and is conducive to the hydrogenation reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the XRD diagram of the aluminum oxide-titanium oxide composite oxide prepared in Example 1 and Comparative Example 1;

[0018] Figure 2 It is the infrared skeleton diagram of the aluminum oxide-titanium oxide composite oxide prepared in Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] A first aspect of the present invention provides a method for preparing an aluminum oxide-titanium oxide composite oxide, wherein the method comprises the following steps:

[0021] (1) subjecting an acidic solution containing aluminum and titanium to a colloid reaction with an alkaline solution containing aluminum to obtain a solid colloid product;

[0022] (2) subjecting the solid gel-forming product obtained in step (1) to an aging reaction in the presence of a precipitant to obtain an aging reaction product;

[0023] (3) subjecting the aging reaction product obtained in step (2) to hydrothermal treatment, followed by drying and calcining to obtain an aluminum oxide-titanium oxide composite oxide;

[0024] Among them, the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction.

[0025] Compared with the prior art, the method provided by the present invention can realize the preparation of aluminum oxide-titanium oxide composite oxide by combining coprecipitation method with hydrothermal method and controlling reaction conditions without using organic titanium-containing reagent. The present invention can carry out aging reaction at a relatively low temperature and then carry out hydrothermal treatment at a higher temperature by controlling aging reaction and hydrothermal treatment conditions. The aluminum oxide-titanium oxide composite oxide prepared by the present invention has a relatively low titanium oxide content, anatase-type titanium oxide, a relatively high pore concentration and a suitable range of the most probable pore diameter, and is particularly suitable for a carrier of a hydrogenation catalyst.

[0026] In the present invention, there is no particular limitation on the method for preparing the acidic solution containing aluminum and titanium, as long as the acidic solution can be obtained by dissolving the titanium-containing compound in the aluminum solution. Preferably, in step (1), the acidic solution containing aluminum and titanium is obtained by dissolving the titanium-containing compound in the acidic aluminum solution.

[0027] In the present invention, there is no particular limitation on the type of titanium-containing compound, as long as it can meet the requirements of the colloid reaction. Preferably, the titanium-containing compound is titanyl sulfate and / or titanium sulfate. By selecting the titanium-containing compound within the above range to prepare the acidic solution containing titanium and aluminum for the colloid reaction, the use of organic titanium reagents is avoided, ensuring that the entire preparation process is simple and environmentally friendly.

[0028] In the present invention, there is no particular limitation on the type of the acidic aluminum solution. Preferably, the acidic aluminum solution is selected from at least one of an aluminum sulfate solution, an aluminum nitrate solution, and an aluminum chloride solution.

[0029] In the present invention, there is no particular limitation on the type of aluminum-containing alkaline solution, as long as a gelling reaction can be achieved. Preferably, in step (1), the aluminum-containing alkaline solution is a sodium aluminate solution and / or a potassium aluminate solution.

[0030] In the present invention, the ratio of titanium and aluminum is controlled by regulating the concentration of the acidic solution containing aluminum and titanium, the titanium content is controlled, and aluminum oxide-titanium oxide composite oxides in different ranges are prepared to meet different application scenarios. Preferably, in step (1), in the acidic solution containing aluminum and titanium, the concentration of the acidic solution containing aluminum and titanium in terms of aluminum oxide is 35-120 g / L, for example, it can be 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, 110 g / L, 115 g / L, 120 g / L and values ​​between any two groups. Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium in terms of titanium oxide is 5-80 g / L, for example, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L and values ​​between any two groups.

[0031] In the present invention, there is no particular limitation on the concentration of the aluminum-containing alkaline solution, as long as the requirements of the gelling reaction are met. Preferably, the concentration of the aluminum-containing alkaline solution is 20-300 g / L, calculated as alumina, for example, it can be 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 250 g / L, 260 g / L, 270 g / L, 280 g / L, 290 g / L, 300 g / L and values ​​between any two groups.

[0032] In the present invention, preferably, the amount of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum is such that the aluminum oxide-titanium oxide composite oxide obtained has an aluminum oxide content of 70-99% by weight, preferably 75-96% by weight, and a titanium oxide content of 1-30% by weight, preferably 5-25% by weight, based on the total amount of the aluminum oxide-titanium oxide composite oxide. It should be noted that a small amount of impurities may exist in the aluminum oxide-titanium oxide composite oxide, so when impurities exist, the contents of aluminum oxide, titanium oxide and impurities satisfy that the sum is equal to 100%. In the present invention, the types of impurities are not specifically limited, for example, SO3, Na2O, etc.

[0033] In the present invention, there is no particular limitation on the method of the gelling reaction, and it can be a method conventionally defined in the art. Preferably, in step (1), the gelling reaction is carried out in a continuous or intermittent manner, preferably in a continuous manner. On the one hand, the gelling reaction carried out in a continuous manner is more conducive to controlling the pH of the gelling reaction process and effectively improving the quality of the aluminum oxide-titanium oxide composite oxide. On the other hand, continuous operation can increase the processing volume per unit time and improve production efficiency.

[0034] The present invention has no particular limitation on the equipment for the gelling reaction, and it can be any conventional choice in the art. Specifically, for example, it can be carried out in a gelling tank.

[0035] According to a preferred specific embodiment of the present invention, the process of conducting a gelling reaction in a continuous manner in the present invention includes: adding a certain amount of deionized water in a gelling tank in advance, and introducing an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum from the top of the gelling tank, so that the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are mixed and contacted to conduct a gelling reaction, and the slurry generated by the gelling reaction continuously flows out of the gelling tank, and the liquid level in the gelling tank is controlled to remain unchanged.

[0036] In the present invention, the conditions for the gelling reaction are relatively wide. Preferably, in step (1), the conditions for the gelling reaction include: a temperature of 50-70°C and a pH value of 4-7. In this preferred embodiment, it is more conducive to improving the quality of the aluminum oxide-titanium oxide composite oxide. In the present invention, during the gelling reaction, the pH value should not be too high. Too high a gelling reaction pH will result in low pore volume and specific surface area of ​​the titanium aluminum composite oxide product; the pH of the gelling reaction should not be too low, because a lower gelling reaction pH is likely to result in large differences in the generation rates of hydrated oxides of aluminum and titanium, which is not conducive to the uniform dispersion of titanium in aluminum oxide. In the present invention, there is no particular limitation on the method for controlling the pH. For example, the flow rate of the acidic solution containing aluminum and titanium and the precipitant can be adjusted. In the present invention, there is no particular limitation on the flow rate of the acidic solution containing aluminum and titanium and the precipitant, as long as the pH value of the gelling reaction is met.

[0037] In the present invention, the pH value of the reaction system is regulated by adding a precipitant, so that the slurry of the solid gelled product obtained in step (1) after beating is subjected to an aging reaction. The present invention has a wide range of selection of precipitants. Preferably, in step (2), the precipitant is selected from a compound containing an alkali metal, preferably selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate. In the present invention, there is no particular limitation on the amount of the precipitant, and it is sufficient to limit the pH value required for the aging reaction. Those skilled in the art can select according to actual needs.

[0038] In the present invention, the range of conditions for the aging reaction is relatively wide. Preferably, in step (2), the conditions for the aging reaction include: temperature of 60-98°C, time of 4-9h, and pH of 7-11; further preferably, in step (2), the conditions for the aging reaction include: temperature of 70-95°C, time of 5-8h, and pH of 7.5-10. By controlling the conditions for the aging reaction, the pore structure of the alumina-titanium oxide composite oxide is regulated, thereby improving the quality of the alumina-titanium oxide composite oxide.

[0039] In the present invention, preferably, after the aging treatment, step (2) further comprises solid-liquid separation of the aged product to obtain a solid aged product. In the present invention, the solid-liquid separation is a conventional operation in the art, specifically, for example, at least one of sedimentation, filtration and centrifugal separation, and those skilled in the art can select according to actual needs.

[0040] In the present invention, preferably, the temperature of the hydrothermal treatment is 10-100°C higher than the temperature of the aging reaction, preferably 10-80°C higher, more preferably 20-70°C higher, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C and values ​​between any two groups. By controlling the temperature of the aging reaction and the hydrothermal treatment, the pore concentration of the aluminum oxide-titanium oxide composite oxide can be increased, and anatase crystal form can be obtained. When the temperature difference between the two is not within the above preferred range, the grain size of the aluminum oxide-titanium oxide composite oxide is larger, which affects the specific surface area and the most probable pore size of the composite oxide material.

[0041] In the present invention, preferably, before the hydrothermal treatment, step (3) further comprises washing the solid aged product. In the present invention, the washing operation is a conventional operation in the art, and it is only necessary to reduce the content of impurity ions (such as residual sodium and sulfate) in the solid aged product, for example, so that the content of sodium oxide in the obtained aluminum oxide-titanium oxide composite oxide is less than 0.1% by weight, preferably less than 0.06% by weight, and more preferably 0.01-0.05% by weight.

[0042] In the present invention, preferably, step (3) comprises: adding water (preferably deionized water) to the solid aged product after the aging treatment, slurrying and then performing hydrothermal treatment. In the present invention, the amount of water used is such that the concentration of the slurry obtained after slurrying is 50-180 g / L, preferably 70-150 g / L, based on the weight of the oxides (the total amount of aluminum oxide and titanium oxide).

[0043] Under the premise that the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction, the selection range of the conditions for the hydrothermal treatment is relatively wide, in order to further optimize the pore structure characteristics of the alumina-titanium oxide composite oxide. Preferably, in step (3), the conditions for the hydrothermal treatment include: a temperature of 100-180°C and a time of 2-9h. In the present invention, the hydrothermal treatment can change the state of existence of titanium dioxide on alumina, and the coprecipitation method is combined with the hydrothermal method, which not only improves the pore concentration of the alumina-titanium oxide composite oxide, so that the most probable pore diameter falls within a suitable range, but also allows the titanium dioxide dispersed in the alumina skeleton to aggregate to form anatase, which is more conducive to improving the activity of the hydrogenation reaction, and obtains anatase-γ-Al2O3 carrier with a low titanium dioxide content.

[0044] In the present invention, the drying conditions have a wide range of selections. Preferably, the drying conditions include: a temperature of 60-200°C, more preferably 100-160°C.

[0045] In the present invention, the range of calcination conditions is relatively wide. Preferably, in step (3), the calcination conditions include: a temperature of 500-700°C for 2-6 hours, more preferably 550-650°C for 3-5 hours.

[0046] In the present invention, preferably, the method does not require the use of organic titanium-containing reagents. The present invention prepares aluminum oxide-titanium oxide composite oxide materials by coprecipitation and hydrothermal treatment, has a simple reaction process, is easy to operate, uses cheap and readily available raw materials, does not require organic reagents, and has an environmentally friendly production process.

[0047] The second aspect of the present invention provides an aluminum oxide-titanium oxide composite oxide prepared by the method described in the first aspect.

[0048] In the present invention, preferably, in the aluminum oxide-titanium oxide composite oxide, based on the total amount of the aluminum oxide-titanium oxide composite oxide, the content of the aluminum oxide is 70-99% by weight, and the content of the titanium oxide is 1-30% by weight; further preferably, based on the total amount of the aluminum oxide-titanium oxide composite oxide, the content of the aluminum oxide is 75-96% by weight, and the content of the titanium oxide is 4-25% by weight. It should be noted that a small amount of impurities may exist in the aluminum oxide-titanium oxide composite oxide, so when impurities exist, the contents of aluminum oxide, titanium oxide and impurities satisfy that the sum is equal to 100%. In the present invention, the type of impurities is not specifically limited, for example, it can be SO3, Na2O, etc.

[0049] In the present invention, the composition of the aluminum oxide-titanium oxide composite oxide is determined by measuring the characteristic spectral lines of each element using a 3271 X-ray fluorescence spectrometer produced by Rigaku Corporation, and semi-quantitatively analyzing the element content of the aluminum oxide-titanium oxide composite oxide using an external standard method.

[0050] In the present invention, preferably, the titanium oxide is anatase type and the aluminum oxide is γ crystalline. The method of the present invention can realize the preparation of anatase type aluminum oxide-titanium oxide composite oxide carrier with low titanium content in the absence of an organic titanium reagent.

[0051] In the present invention, it can be seen from the XRD diffraction spectrum that the titanium oxide has typical anatase diffraction peaks at 25.3°, 48.1°, 54°, and 55.1°, indicating that the titanium oxide is in anatase crystal form.

[0052] In the present invention, the crystal structure of the aluminum oxide-titanium oxide composite oxide is measured by using a Philips XPERT series X-ray powder diffractometer.

[0053] The aluminum oxide-titanium oxide composite oxide prepared by the preparation method provided by the present invention has a lower titanium oxide content, and the titanium oxide is anatase-type, thereby realizing the preparation of anatase-type composite oxide with a lower titanium oxide content, and being more conducive to the preparation of hydrogenation carriers.

[0054] The aluminum oxide-titanium oxide composite oxide provided by the present invention has a high pore concentration, which is conducive to the hydrogenation reaction. Preferably, the aluminum oxide-titanium oxide composite oxide has a pore volume of 0.4-1.3 mL / g and a specific surface area of ​​200-400 m 2 / g, the most probable pore size is 5-12nm; further preferably, the pore volume of the alumina-titanium oxide composite oxide is 0.5-0.9mL / g, and the specific surface area is 220-300m 2 / g, and the most probable pore size is 7-11nm.

[0055] In the present invention, the pore structure characteristics of the aluminum oxide-titanium oxide composite oxide are measured by N2 adsorption and desorption characterization on a Micromeritics ASAP2420 adsorption instrument.

[0056] The third aspect of the present invention provides a use of the aluminum oxide-titanium oxide composite oxide described in the second aspect in a hydrodesulfurization reaction. Preferably, the aluminum oxide-titanium oxide composite oxide is used as a catalyst carrier in a hydrogenation reaction.

[0057] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0058] The composition of the aluminum oxide-titanium oxide composite oxide was determined by using the Rigaku Corporation 3271 X-ray fluorescence spectrometer to measure the characteristic spectral lines of each element. The element content of the titanium aluminum composite oxide was semi-quantitatively analyzed by the external standard method to obtain the composition of Al2O3, TiO2, SO3, Na2O, etc. in the sample.

[0059] The N2 adsorption and desorption characterization method is as follows: N2 adsorption and desorption characterization is performed on a Micromeritics ASAP 2420 adsorption instrument. Before the test, about 0.3 g of alumina-titania composite oxide powder is taken and pretreated at 350° C. and vacuum conditions for 10 hours.

[0060] The crystal form characterization method of aluminum oxide-titanium oxide composite oxide is as follows: a certain amount of aluminum oxide-titanium oxide composite oxide powder is pressed into a sheet, and the crystal form of the sample is determined by a Philips XPERT series X-ray powder diffractometer. The test conditions are: Cu Kα ray (Kα = 0.154nm), working current 30mA, working voltage 40kV, Ni filter, scanning range 2θ = 5°-70°.

[0061] The infrared skeleton characterization method of aluminum oxide-titanium oxide composite oxide is as follows: a certain amount of aluminum oxide-titanium oxide composite oxide powder is added with KBr and pressed into a sheet, and a Nicolet 6700 infrared spectrometer produced by Thermo Fisher Scientific is used with a resolution of 4 cm -1 , scanning range 4000-400cm -1 , scanned 32 times, and the infrared spectrum of aluminum oxide-titanium oxide composite oxide was obtained by single-point attenuated total reflection method.

[0062] Example 1

[0063] (1) 3 L of deionized water is added to a gelling tank in advance, titanyl sulfate is added to an aluminum sulfate solution to prepare an acidic solution containing aluminum and titanium, the acidic solution containing aluminum and titanium and a sodium aluminate solution are introduced from the top of the gelling tank, and the acidic solution containing aluminum and titanium and the sodium aluminate solution are mixed in the gelling tank to perform a gelling reaction, and the slurry after the gelling reaction flows out from the overflow pipe of the gelling tank, and the liquid level in the gelling tank remains unchanged. When the deionized water added in advance is replaced by the slurry after the gelling reaction, the slurry is collected, and then filtered to obtain a filter cake (solid gelling product);

[0064] Among them, the concentration of sodium aluminate solution (calculated as alumina) is 200g / L, the flow rate is 42g / min, the titanium oxide concentration in the acidic solution containing aluminum and titanium is 12.89g / L, and the alumina concentration is 58g / L. By adjusting the flow rate of the acidic solution containing aluminum and titanium to 115-125g / min, the pH value of the gelation reaction process is about 6.3, and the temperature of the gelation reaction is 60°C.

[0065] (2) The gelling reaction product is subjected to an aging treatment, and the pH of the aging treatment is adjusted by adding a sodium carbonate solution. The aging treatment conditions are pH 9.0, temperature 90° C., and time 6 h.

[0066] (3) The aged mixture was filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) was added to deionized water for slurrying. The concentration of the obtained slurry was 130 g / L based on the weight of the titanium oxide-aluminum oxide composite oxide. The obtained slurry was hydrothermally treated at a temperature of 150°C for 4 hours. After the hydrothermal treatment, the aluminum oxide-titanium oxide composite oxide A1 was obtained after spray drying and calcination at 600°C for 3 hours. The composition of the aluminum oxide-titanium oxide composite oxide A1 was 10% by weight of titanium oxide and 88.7% by weight of aluminum oxide, and the rest was trace impurities from the synthesis process and the analysis process. The specific physicochemical properties are listed in Table 1. Figure 1 The XRD patterns of Example 1 and Comparative Example 1 are shown in Table 1. Figure 1 It can be seen that in Example 1, the titanium oxide is in an anatase crystal form (diffraction peaks appear at 25.3°, 48.1°, 54°, and 55.1° of titanium oxide, indicating that the titanium oxide is in an anatase crystal form), and the aluminum oxide is in a γ-Al2O3 crystal form (diffraction peaks appear at 36°, 45°, and 67° of aluminum oxide, indicating that the aluminum oxide is in a γ-Al2O3 crystal form). Figure 2 This is the result of infrared skeleton analysis, where 1100cm -1 The peak at is the characteristic peak of Al-O bond. Figure 2 It can be seen that the characteristic vibration peak of the Al-O bond in Example 1 disappears, indicating that the Ti in Example 1 partially replaces the Al in the alumina structure, affecting the chemical environment around the Al atoms, and further affecting the reaction activity of the catalyst prepared using the alumina-titanium oxide composite oxide as a carrier.

[0067] Comparative Example 1

[0068] The method of Example 1 is followed, except that after the aging in step (2) is completed, no hydrothermal treatment is performed, and the aged mixture is filtered, washed, spray-dried, and then calcined at 600°C for 3 hours to obtain aluminum oxide-titanium oxide composite oxide S1. The final composition of aluminum oxide-titanium oxide composite oxide S1 is 10 wt% titanium oxide and 88.7 wt% aluminum oxide, and the rest is trace impurities from the synthesis and analysis processes. The specific physical and chemical properties are listed in Table 1. Figure 1 It can be seen that no anatase crystal form is detected. The alumina in Comparative Example 1 is in the γ-Al2O3 crystal form.

[0069] Comparative Example 2

[0070] This comparative example adopts the preparation method in the existing technical document ("Effects of the addition of titania on the ethermal characterization of alumina-supported palladium", Journal of Molecular Catalysis A, 2002, 180, 285-291) to prepare titanium oxide-aluminum oxide composite oxide. Take 20g of γ-Al2O3 (Sinopec Changling Catalyst Co., Ltd.), and take another 7.74g of isopropyl titanate and dissolve it in propanol, quantify it to 15mL and stir it thoroughly. Then disperse γ-Al2O3 in the isopropanol solution of the above-mentioned isopropyl titanate, dry it at 110°C overnight, and calcine it at 550°C for 3 hours to obtain aluminum oxide-titanium oxide composite oxide S2. The composition of aluminum oxide-titanium oxide composite oxide S2 is 10.8% by weight of titanium oxide and 87.0% by weight of aluminum oxide, and the rest is trace impurities in the synthesis process and analysis process. The specific physical and chemical properties are listed in Table 1. Compared with Example 1, the composite oxide crystal form prepared by this method is anatase-γ-Al2O3. Figure 2 The infrared skeleton analysis results show that compared with pure alumina support, the -1 The characteristic peak of the Al-O bond did not change, indicating that the organic impregnation method would not affect the skeleton structure of alumina.

[0071] Example 2

[0072] The method of Example 1 is followed, except that in step (1), the concentration of titanium oxide in the acidic solution containing aluminum and titanium is 20.67 g / L, the concentration of aluminum oxide is 46.64 g / L, and the flow rate is 110-120 g / min. The remaining conditions are the same as those of Example 1. The resulting slurry is hydrothermally treated at 150°C for 4 hours, filtered, dried at 120°C for 6 hours, and calcined at 600°C for 3 hours to obtain aluminum oxide-titanium oxide composite oxide A2, which is composed of 19.3% by weight of titanium oxide and 79.5% by weight of aluminum oxide, and the rest are trace impurities in the synthesis process and the analysis process. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Example 2 is the same as in Example 1 and is in the γ-Al2O3 crystal form.

[0073] Example 3

[0074] The method of Example 2 is followed, except that the temperature during the hydrothermal treatment in step (3) is 130°C and the hydrothermal time is 4 hours. The composition of the aluminum oxide-titanium oxide composite oxide A3 is 19.3% by weight titanium oxide and 79.5% by weight aluminum oxide, and the rest is trace impurities in the synthesis and analysis processes. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Example 3 is the same as in Example 1 and is in the γ-Al2O3 crystal form.

[0075] Example 4

[0076] The method of Example 2 is followed, except that the temperature during the hydrothermal treatment in step (3) is 110° C. and the hydrothermal time is 4 h. The composition of the aluminum oxide-titanium oxide composite oxide A4 is 19.3 wt % titanium oxide and 79.5 wt % aluminum oxide, and the rest is trace impurities in the synthesis and analysis processes. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Example 4 is the same as in Example 1 and is in the γ-Al2O3 crystal form.

[0077] Example 5

[0078] The method of Example 2 is followed, except that the aging treatment temperature in step (2) is 60° C. The composition of the aluminum oxide-titanium oxide composite oxide A5 is 19.3 wt % titanium oxide and 79.5 wt % aluminum oxide, and the rest is trace impurities in the synthesis and analysis processes. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Example 5 is the same as in Example 1 and is in the γ-Al2O3 crystal form.

[0079] Example 6

[0080] The method of Example 1 is followed, except that in step (1), the concentration of titanium oxide in the acidic solution containing aluminum and titanium is 31.75 g / L, and the concentration of aluminum oxide is 46.64 g / L. The remaining conditions are the same as those of Example 1. The resulting slurry is hydrothermally treated at 120°C for 4 hours, filtered, dried at 120°C for 6 hours, and calcined at 600°C for 3 hours to obtain aluminum oxide-titanium oxide composite oxide A6, which is composed of 29.3% by weight of titanium oxide and 70.5% by weight of aluminum oxide, and the rest are trace impurities in the synthesis process and the analysis process. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Example 6 is the same as in Example 1 and is in the γ-Al2O3 crystal form.

[0081] Example 7

[0082] (1) The method of Example 1 is followed, except that in step (1), an acidic solution containing aluminum and titanium with different titanium oxide contents is used. Specifically, the titanium oxide concentration is 6.11 g / L, the aluminum oxide concentration is 58 g / L, and the flow rate is 120-130 g / min.

[0083] (2) subjecting the gelling reaction product to an aging treatment, wherein the aging treatment conditions are as follows: pH 8.0, temperature 70° C., time 8 h, and the concentration of the aging mixture is 70 g / L based on titanium oxide-aluminum oxide.

[0084] (3) The aged mixture was filtered and washed in order to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) was added to deionized water for slurrying. The concentration of the obtained slurry was 130 g / L in terms of titanium oxide-aluminum oxide. The obtained slurry was subjected to hydrothermal treatment at a temperature of 170° C. for 4 hours. After the hydrothermal treatment, the mixture was spray dried and calcined at 600° C. for 3 hours to obtain aluminum oxide-titanium oxide composite oxide A7. The composition of aluminum oxide-titanium oxide composite oxide A7 was 5.3% by weight of titanium oxide and 94.2% by weight of aluminum oxide, and the rest was trace impurities in the synthesis process and the analysis process. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Example 7 was in the γ-Al2O3 crystal form as in Example 1.

[0085] Comparative Example 3

[0086] The method of Example 2 is used, except that the hydrothermal treatment in step (3) is not performed. After aging, the filter cake is filtered and washed to obtain a filter cake, which is dried at 120°C for 6 hours and calcined at 600°C for 3 hours to obtain an aluminum oxide-titanium oxide composite oxide S3. The composition of the aluminum oxide-titanium oxide composite oxide S3 is 19.3% by weight of titanium oxide and 79.5% by weight of aluminum oxide, and the rest is trace impurities in the synthesis process and the analysis process. The specific physical and chemical properties are listed in Table 1. The aluminum oxide in Comparative Example 3 is the same as that in Example 1 and is in the γ-Al2O3 crystal form.

[0087] Comparative Example 4

[0088] This embodiment adopts the titration precipitation method in patent application CN111050904A to prepare titanium oxide-aluminum oxide composite oxide. Sodium aluminate is diluted in water, and aluminum sulfate and titanyl sulfate are added under vigorous stirring and heating at 60°C, and the final pH value is 6.5. Use NaOH to adjust the pH to 7.2, and age the mixture at 60°C for 1 hour under stirring. The filter cake is re-slurried with water, adjusted to pH 10 with ammonia water, and aged at 95°C for 1 hour under stirring. Then, the slurry is filtered and washed with water to remove excess ammonia, dried, extruded, and roasted at 650°C for 1 hour at an air flow of 10mL / min and 25% (volume ratio) steam to obtain aluminum oxide-titanium oxide composite oxide S4, which is composed of 10.4% by weight of titanium oxide and 88.9% by weight of aluminum oxide, and the rest are trace impurities in the synthesis process and analysis process. The specific physicochemical properties are listed in Table 1. In Comparative Example 4, the aluminum oxide is the same as in Example 1 and is in the γ-Al2O3 crystal form.

[0089] Table 1

[0090]

[0091]

[0092] It can be seen from the results in Table 1 that Examples 1-7 prepared by the method of the present invention all have anatase-γ-Al2O3 crystal form. When the preparation conditions are within the preferred range of the present invention, the most probable pore size of the aluminum oxide-titanium oxide composite oxide material is moderate and has a better specific surface area. Compared with the comparative example, the raw materials for preparing the aluminum oxide-titanium oxide composite oxide material by the method of the present invention are cheap and easy to obtain, the preparation process is simple, and the process is short to obtain the composite oxide material of the anatase-γ-Al2O3 crystal form.

[0093] Test Case

[0094] The alumina-titanium oxide composite oxides of the above-mentioned Examples 1-7 and Comparative Examples 1-4 were saturated with a mixed solution of ammonium molybdate heptahydrate, ammonia water and cobalt nitrate to contain 12.0 wt% of molybdenum oxide and 2.5 wt% of cobalt oxide, respectively. After drying, they were calcined at 450°C for 3 hours to prepare a hydrodesulfurization catalyst.

[0095] In a fixed-bed continuous flow micro-reaction device, a decane solution containing 1.0 mass% DBT (dibenzothiophene) and 1.0 mass% decalin is used as the raw oil, and the catalyst is loaded into the constant temperature zone of the micro fixed-bed reactor. The catalyst needs to be pre-sulfurized before the reaction. The sulfiding oil is a cyclohexane solution containing 5% CS2 (mass fraction), the sulfiding temperature is 360°C, the hydrogen flow rate is 365mL / min, the sulfiding oil flow rate is 0.4mL / min, and the sulfiding pressure is 4MPa. After the sulfidation is completed, switch to the reaction oil. The hydrogenation reaction conditions are a reaction temperature of 240°C, a reaction pressure of 4MPa, a hydrogen flow rate of 100mL / min, a reaction oil flow rate of 0.2mL / min, and a volume space velocity of 40h -1 After the system was stabilized, the product condensate was collected and the product composition was analyzed by GC-MS.

[0096] The conversion rate x of DBT was calculated according to the following formula:

[0097]

[0098] Wherein, a is the mass fraction of DBT in the product, and b is the mass fraction of DBT in the raw material. The conversion rate data are shown in Table 2.

[0099] Table 2

[0100] DBT conversion rate (%) Example 1 79.22 Comparative Example 1 75.34 Comparative Example 2 74.17 Example 2 81.35 Example 3 84.46 Example 4 86.21 Example 5 77.02 Example 6 75.65 Example 7 76.12 Comparative Example 3 75.86 Comparative Example 4 65.17

[0101] It can be seen from Table 2 that when the aluminum oxide-titanium oxide composite oxide material prepared by the method provided by the present invention is used to prepare a catalyst, the catalyst has better reaction activity under the same other conditions and can improve the conversion rate of the reaction raw materials.

[0102] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing an aluminum oxide-titanium oxide composite oxide, characterized in that: The method comprises the following steps: (1) subjecting an acidic solution containing aluminum and titanium to a colloid reaction with an alkaline solution containing aluminum to obtain a solid colloid product; (2) subjecting the solid gel-forming product obtained in step (1) to an aging reaction in the presence of a precipitant to obtain an aging reaction product; (3) subjecting the aging reaction product obtained in step (2) to hydrothermal treatment, followed by drying and calcining to obtain an aluminum oxide-titanium oxide composite oxide; Among them, the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction.

2. The method according to claim 1, wherein: In step (1), the acidic solution containing aluminum and titanium is prepared by dissolving a titanium-containing compound in an acidic aluminum solution; Preferably, the titanium-containing compound is titanyl sulfate and / or titanium sulfate; Preferably, the acidic aluminum solution is selected from at least one of an aluminum sulfate solution, an aluminum nitrate solution and an aluminum chloride solution; Preferably, in step (1), the aluminum-containing alkaline solution is a sodium aluminate solution and / or a potassium aluminate solution; Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium is 35-120 g / L in terms of alumina; Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium is 5-80 g / L in terms of titanium oxide; Preferably, in step (1), the concentration of the aluminum-containing alkaline solution is 20-300 g / L in terms of aluminum oxide; Preferably, the amounts of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are such that the aluminum oxide-titanium oxide composite oxide obtained has an aluminum oxide content of 70-99% by weight, preferably 75-96% by weight, and a titanium oxide content of 1-30% by weight, preferably 4-25% by weight, based on the total amount of the aluminum oxide-titanium oxide composite oxide.

3. The method according to claim 1 or 2, wherein: In step (1), the gelling reaction is carried out in a continuous or intermittent manner, preferably in a continuous manner; Preferably, in step (1), the conditions for the gelling reaction include: a temperature of 50-70° C. and a pH value of 4-7.

4. The method according to any one of claims 1 to 3, wherein: In step (2), the precipitant is selected from a compound containing an alkali metal, preferably at least one selected from sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; Preferably, in step (2), the conditions of the aging reaction include: temperature of 60-98°C, time of 4-9h, pH value of 7-11; Further preferably, in step (2), the conditions of the aging reaction include: temperature of 70-95°C, time of 5-8h, and pH value of 7.5-10.

5. The method according to any one of claims 1 to 4, wherein: The temperature of the hydrothermal treatment is 10-100°C higher than the temperature of the aging reaction, preferably 10-80°C higher, more preferably 20-70°C higher.

6. The method according to any one of claims 1 to 5, wherein: In step (3), the conditions of the hydrothermal treatment include: temperature 100-180°C, time 2-9h; Preferably, in step (3), the calcination conditions include: temperature of 500-700° C. and time of 2-6 h.

7. The method according to any one of claims 1 to 6, wherein: This method does not use organic titanium-containing reagents.

8. Aluminum oxide-titanium oxide composite oxide obtained by the method according to any one of claims 1 to 7; Preferably, in the aluminum oxide-titanium oxide composite oxide, based on the total amount of the aluminum oxide-titanium oxide composite oxide, the content of the aluminum oxide is 70-99% by weight, and the content of the titanium oxide is 1-30% by weight; Further preferably, based on the total amount of the aluminum oxide-titanium oxide composite oxide, the aluminum oxide content is 75-96% by weight, and the titanium oxide content is 4-25% by weight; Preferably, the titanium oxide is anatase type, and the aluminum oxide is γ crystalline.

9. The aluminum oxide-titanium oxide composite oxide according to claim 8, wherein The pore volume of the aluminum oxide-titanium oxide composite oxide is 0.4-1.3 mL / g, and the specific surface area is 200-400 m 2 / g, the most probable pore size is 5-12nm; Preferably, the pore volume of the alumina-titanium oxide composite oxide is 0.5-0.9 mL / g and the specific surface area is 220-300 m 2 / g, and the most probable pore size is 7-11nm.

10. Use of the aluminum oxide-titanium oxide composite oxide according to claim 8 or 9 in a hydrodesulfurization reaction.

Citation Information

Patent Citations

  • Hydrotreating catalyst with a titanium containing carrier and organic additive

    CN111050904A

  • Alumina-titania composition

    EP0339640A1

  • Preparation method of hydrogenation catalyst containing molecular sieve

    CN103100410A

  • Preparation method of titanium-aluminum composite oxide with large specific surface and small aperture

    CN104475168A

  • Preparation method of large-aperture titanium-aluminum composite oxide

    CN105170193A